2015
DOI: 10.17957/ijab/14.0027
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Analysis of Mosquitoes from Rural and Urban Areas of Sialkot, Pakistan

Abstract: The current study was conducted to demonstrate the genetic variability, gene flow and rate of migration in mosquito populations between rural and urban areas in Sialkot, Pakistan. The adult mosquitoes were collected with the help of sweep net and battery-operated aspirator, whereas the larvae were collected using standard dippers. DNA extraction was performed through TNE salt extraction method. Fourteen samples of mosquito populations for the selected seven species of three genera were studied using RAPD loci.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…Our results showed that the studied C. pipiens complex populations were genetically less differentiated (G ST = 0.07), having a high level of gene flow (Nm = 6.61) among them. These low G ST and high Nm values detected in the present study are consistent with the findings of many studies reported for different mosquito species from different parts of the world (Lehmann et al, 1996;Besansky et al, 1997;Humeres et al, 1998;Cui et al, 2007;Santos et al, 2011;Bibi et al, 2015;Preet and Gupta, 2017). In their study, Cui et al (2007) compared the previous population genetic surveys of C. pipiens in different geographic areas around the world and reached a conclusion that this species needs considerable distances, at least between 500 and 1000 km, to show isolation by distance, irrespective of the subspecies (C. p. pipiens, C. p. quinquefasciatus, and C. p. pallens) or the geographic location.…”
Section: Discussionsupporting
confidence: 93%
“…Our results showed that the studied C. pipiens complex populations were genetically less differentiated (G ST = 0.07), having a high level of gene flow (Nm = 6.61) among them. These low G ST and high Nm values detected in the present study are consistent with the findings of many studies reported for different mosquito species from different parts of the world (Lehmann et al, 1996;Besansky et al, 1997;Humeres et al, 1998;Cui et al, 2007;Santos et al, 2011;Bibi et al, 2015;Preet and Gupta, 2017). In their study, Cui et al (2007) compared the previous population genetic surveys of C. pipiens in different geographic areas around the world and reached a conclusion that this species needs considerable distances, at least between 500 and 1000 km, to show isolation by distance, irrespective of the subspecies (C. p. pipiens, C. p. quinquefasciatus, and C. p. pallens) or the geographic location.…”
Section: Discussionsupporting
confidence: 93%
“…Further, molecular studies based on DNA analysis of mosquitoes in Pakistan had established a barcode reference library for the mosquitoes of this region [39]. The levels of genetic diversity varied among species and DNA barcoding supported an accurate tracking of mosquito populations [33]. Further, the present research was of restricted retro and not the only effort to statistical recitation abundance to concurrent quantification of biotic and abiotic variable shreds of evidence on population dynamics over a vast locality.…”
Section: Discussionmentioning
confidence: 78%
“…Notably, earlier information on the distribution of Ae. aegypti showing all the localities of species, density and seasonal prevalence in the subcontinent and South-East Asia was provided [13,[33][34]. In the literature concerning the mosquitoes of Pakistan, a specification gradient has arranged 134 existing mosquito species [35].…”
Section: Discussionmentioning
confidence: 99%
“…The DNA from supernatant was precipitated by adding ice cold ethanol in equal volume, and kept at −20 °C for 1 hour and afterwards recovered by centrifugation. The DNA pellet was air dried and resuspended in D 3 H 2 O [38][39][40] .…”
Section: Phytochemical Analysis Of Weeds Extracts Phytochemical Analmentioning
confidence: 99%
“…= × µ µ DNA Conc g/ l Dilution fold absorbance at 260 nm RAPD-PCR amplification. A total of five RAPD primers (GenLink: A-03, A-04, A-06, A-18 and C-04; Supplementary Table) were selected to amplify the mosquitoes genomic DNA following the PCR conditions as described by Bibi et al 39 and Zahoor et al 41 .…”
Section: Phytochemical Analysis Of Weeds Extracts Phytochemical Analmentioning
confidence: 99%